Design of Measurement of Coffee Seed Water Content Using Load Cell Sensor On Coffee Dryer - Muhammad Mistu Adi Putra; Amalia Herlina (Universitas Ahmad Dahlan, 2020)
The conventional method of drying coffee beans that depend on sunlight (drying) has a number of drawbacks, one of which is that the drying productivity takes a long time. In general, coffee drying is carried out until it reaches a moisture content of 12.5% to achieve a quality bean standard. Mathematically, the moisture content can be assessed by paying attention to the initial weight of the coffee beans and the final weight of the coffee beans. So that the use of the Load Cell sensor to read the depreciation value of the coffee bean weight on a coffee dryer powered by Hybrid Collector and LPG coffee beans. Research that has been carried out during 200 minutes of drying in a coffee dryer, the Load Cell sensor is able to read the depreciation value of the coffee bean weight by 114 grams from the initial weight of 978 grams. Therefore, it can be concluded that the final moisture content of coffee beans has reached 12.01% and the final weight of coffee beans is 864 grams.